Beyond Beneficence: Moral Asymmetry and the Minimization of Suffering in End-of-Life Care - Braus, Adam (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
This paper critically examines the ethical foundations for minimizing suffering at the end of life. The reduction of suffering is a major concern in the ethical discourse of end-of-life care. Some thinkers privilege minimizing unwanted and unnecessary suffering at the end of life as much as possible. And yet, many others consider minimizing suffering an insufficient or risky justification for decision-making at the end of life. The desire to minimize suffering is considered equivalent to or entirely contained within utilitarianism or, in bioethics, the principle of beneficence. Here, I argue that it is a mistake to ground the desire to minimize suffering at the end of life in utilitarianism or beneficence, since these are morally symmetrical, and the commitment to minimize suffering is morally asymmetrical. As an alternative, I propose and develop the doctrine of least avoidable suffering (DLAS), which is grounded in negative utilitarianism — aka morally asymmetrical consequentialism. I assess DLAS against a series of end-of-life treatments and demonstrate that it aligns well with the ethical commitments of those who desire to minimize suffering at the end of life. I conclude that DLAS offers people, institutions, and physicians a formal, systematized, and defensible theoretical basis for the desire to minimize suffering at the end of life.